2020
DOI: 10.1177/2049463720973703
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of COVID-19-related lockdown on pain, physical activity and psychological well-being in people with chronic pain

Abstract: Countries across the world imposed lockdown restrictions during the COVID-19 pandemic. It has been proposed that lockdown conditions, including social and physical distancing measures, may disproportionately impact those living with chronic pain and require rapid adaptation to treatment and care strategies. Using an online methodology, we investigated how lockdown restrictions in the United Kingdom impacted individuals with chronic pain (N = 431) relative to a healthy control group (N = 88). Data were collecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
113
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(126 citation statements)
references
References 59 publications
(71 reference statements)
10
113
2
1
Order By: Relevance
“…In this study they investigated how lockdown impacted individuals with chronic pain in United Kingdom. The study results indicated that the perception of pain was increased during the lockdown periods [ 21 ]. In another study, the negative impact of lockdown on pain and physical function in patients with hip and knee osteoarthritis (OA) was observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study they investigated how lockdown impacted individuals with chronic pain in United Kingdom. The study results indicated that the perception of pain was increased during the lockdown periods [ 21 ]. In another study, the negative impact of lockdown on pain and physical function in patients with hip and knee osteoarthritis (OA) was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Quarantine measures have a negative impact on human beings which increases anger and aggression, increases sedentary behaviors and leads to development of musculoskeletal pain [ 18 ]. Few recent studies investigate the impact of lockdown on physical and/or intellectual disability [ 19 ], low back pain [ 18 ], hip and knee osteoarthritis [ 20 ], and physical activity and psychological well-being in people with chronic pain [ 21 ]. But there is scarcity of literature regarding the various effects of the nationwide lockdown on the overall musculoskeletal health in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, virtual or hybrid learning at school has facilitated continuity of education to some degree, but simultaneously, significantly increased children's daily screen time with less opportunity for physical activity, maintaining routines, and social engagement. Self-report data collected during COVID-19 with an adult sample of individuals with CP found that decreases in levels of physical exercise were associated with increased pain [49]. These associations will be important to examine in pediatrics.…”
Section: Physical Activity and Routinesmentioning
confidence: 99%
“…Lockdown is an effective way to prevent the transmission of the COVID-19 virus [10]. Yet it may also have negative effects on the musculoskeletal system [3].…”
Section: Introductionmentioning
confidence: 99%